2019
DOI: 10.1038/s41598-019-43525-8
|View full text |Cite
|
Sign up to set email alerts
|

Automatic discovery of image-based signatures for ipilimumab response prediction in malignant melanoma

Abstract: In the context of precision medicine with immunotherapies there is an increasing need for companion diagnostic tests to identify potential therapy responders and avoid treatment coming along with severe adverse events for non-responders. Here, we present a retrospective case study to discover image-based signatures for developing a potential companion diagnostic test for ipilimumab (IPI) in malignant melanoma. Signature discovery is based on digital pathology and fully automatic quantitative image analysis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
(41 reference statements)
0
40
0
Order By: Relevance
“…Given the success of these and other computer vision models, there is growing interest in whether neural networks can be used to predict response to treatments. In 2019, Harder and colleagues proposed a workflow for predicting response to ipilimumab that relies on DCNNs to robustly segment cell nuclei and classify CD3 þ , CD8 þ , and melanin objects of interest (29). Here, we present an approach to predicting treatment response that similarly draws upon the automated assessment of digital histology images.…”
Section: Discussionmentioning
confidence: 99%
“…Given the success of these and other computer vision models, there is growing interest in whether neural networks can be used to predict response to treatments. In 2019, Harder and colleagues proposed a workflow for predicting response to ipilimumab that relies on DCNNs to robustly segment cell nuclei and classify CD3 þ , CD8 þ , and melanin objects of interest (29). Here, we present an approach to predicting treatment response that similarly draws upon the automated assessment of digital histology images.…”
Section: Discussionmentioning
confidence: 99%
“…2b). Notably, Harder and coworkers classified melanoma patients as responders and non-responders to ipilimumab, 51 and Madabhushi et al demonstrated a concept for the prediction of response to immunotherapy in patients with NSCLC directly from H&E-stained images. 52 However, these studies only included small patient numbers, and it can be expected that the potential of DL to predict therapy response is not yet exhausted.…”
Section: Prediction Of Genotype and Gene Expressionmentioning
confidence: 99%
“…The TIDE and TIS transcriptomic signatures, as well as genes linked to T cells cytotoxicity, Th1 chemokines and antigen presentation seem useful for the identification of responders among melanoma patients ( 29 , 124 ). The mutational and neoantigen load ( 125 ) and a high ratio of CD8 + density in the intratumoral region have also been related to clinical benefit to Ipilimumab in melanoma ( 126 ), while PD-L1 staining by IHC alone does not seem to be predictive ( 127 ).…”
Section: Anti-ctla-4 Inhibitorsmentioning
confidence: 99%